Identification and comprehensive analysis of MIPSs in Rosaceae and their expression under abiotic stresses in rose (Rosa chinensis) - Gangwar, Himanshi; Kumari, Priya; Gahlaut, Vijay; Kumar, Sanjay; Jaiswal, Vandana (Frontiers in Plant Science, 2022)
The Myo-Inositol-1-phosphate synthase (MIPS) gene family is involved in the myo-inositol synthesis and plays a significant role in signal transduction, membrane biogenesis, oligosaccharides synthesis, auxin storage and transport, programmed cell death and abiotic stress tolerance in plants. This study comprehensively identified the MIPS genes in Rosaceae plant species, and 51 MIPS genes were identified from 26 Rosaceae species. The phylogenetic analysis divided the MIPSs into two clades (clade I; subfamily Amygdaloideae specific, and clade II; subfamily Rosoideae specific). MIPS genes of all 26 Rosaceae species consist of similar gene structure, motif and domain composition, which shows their conserved nature. The cis-regulatory elements (CREs) analysis revealed that most Rosaceae MIPS genes play a role in growth, development, and stress responses. Furthermore, the qRT-PCR analysis also revealed the involvement of RcMIPS gene in plant development and response to abiotic stresses, including drought and heat. The results of the present study contribute to the understanding of the biological function of Rosaceae MIPS genes, and that could be used in further functional validations.